A comparative study of posttraumatic stress disorder in two post-conflict communities in Benue state Nigeria - Aladi N. Edeh; Richard Uwakwe; Taiwo J. Obindo; Michael T. Agbir; Oluyemi O. Akanni (Dialogues in Health, 2023)
Background: The attendant long-term mental health consequence of the conflict of various kinds in Nigeria is yet to be thoroughly investigated. The Tiv-Fulani farmer-herdsmen crisis is one such conflict that occurred in 2013/2014 in Guma local government in Benue state. Aims: This study seeks to find out some years after the crisis, the prevalence difference in posttraumatic stress disorder (PTSD) between a community (Uikpiam) with direct exposure to the conflict and another (Daudu) with indirect exposure, the pattern of distribution of PTSD symptoms and the associate factors of PTSD. Methods: It is a cross-sectional one that employed a multi-stage cluster sampling method to select 413 participants; 135 from Uikpiam and 278 from Daudu. The study instruments administered included a questionnaire with some socio-demographic variables and an extract from the PTSD module of the Composite International Diagnostic Interview. Results: The prevalence rate of PTSD was higher in Uikpiam (16.3%) when compared to Daudu (4.3%). A high proportion of sub-threshold symptoms of PTSD was recorded in both communities. An association was found between a lower educational qualification and PTSD (χ2 = 8.373; p = 0.039). Conclusion: PTSD can be a prolonged mental ill-effect of crisis and proximity to trauma sites increases vulnerability including lower education. This study looked at PTSD only as an outcome of this crisis, but mental health adverse outcomes of the crisis may not be limited to this alone, hence the need for further investigations for relevant stakeholders to act.